Design toolkits for campus open spaces from post-occupancy evaluations of federal universities in South-west Nigeria (2018)
Purpose - Participatory design strategy through post-occupancy evaluation of built assets is a feedback mechanism into the design process. This paper draws upon a wider empirical study that aims at evaluating the University Campus Open Spaces (UCOS) of six federal universities in South-west Nigeria. The purpose of this paper is to generate evidence-based design toolkits for UCOS towards spanning of disconnects between designers and users thereby revisiting and revitalizing their design criteria. Design/methodology/approach - A sample (n = 3,016) of users was drawn in a cross-sectional survey through stratified random method. The research instrument was a structured questionnaire in multiple choice and Likert-type scales. The data obtained were subjected to statistical techniques. Findings - Results show that males use the UCOS for active and passive recreation than females. The UCOS are male dominated because the females have higher concerns for lack of safety and inclement weather. Both genders have equal preference for sitting. “Group academic” activities are at peak in the “afternoon”, while “being alone” takes place in the “evening” and “personal academic” in the “morning”. Safety is primary to zoological and botanical gardens. Social interaction spaces enhance successful recreation parks. Coherence and legibility are the highest cognitive satisfaction factors for pedestrian sidewalks. Practical im plications - The research generated design requirements for UCOS, and it is important for informing better design solutions in the future. Originality/value - The results are synthesized into three-in-two new frameworks to guide future design actions for innovative strategies between design and use/operational phases